Pengaruh sayur bayam merah (amaranthus tricolor l) terhadap produksi ASI ibu nifas di Kecamatan Poncokusumo Kabupaten Malang - Patemah Patemah; Ervin Rufaindah (MEDIA ILMU KESEHATAN, 2022)
Background: The National Exclusive Breastfeeding Coverage is 80%. Coverage below 80% is found in 34 Public Health Centers in Malang Regency, one of which is in Poncokusumo Health Center, namely the achievement of exclusive breastfeeding is 77.43%.Objective: The objective of this study was to examine the effect of red spinach on breast milk production for postpartum mothers in Poncokusumo District, Malang Regency.Methods: This type of research is a quasi-experimental with the one group pretest posttest design. The population of this study were postpartum mothers (0-40 days) in Poncokusumo District, as many as 30 people with accidental sampling technique. Giving red spinach for 5 days. In one serving, given 100 grams of red spinach. The analysis of this study was processed using a computerized system, in the form of univariate analysis and bivariate analysis using Mc Nemar's test, with a value of = 0.05.Results: The results of McNemar's analysis found that there was a significant difference between the number of mothers with non-current and smooth milk production after treatment (p 0.000).Conclusions: The results of this study indicate that the treatment of giving red spinach vegetables can increase breast milk production in postpartum mothers in Poncokusumo District, Malang Regency. This is because red spinach (Amaranthus tricolor L) which also contains phytoestrogens in increasing and smoothing breast milk.